(3GdYbjOI GdeajOIs - (3eMeO Hf LQjQ Hf jRjO GdWHQj , GHf LQjQ, CHh LYaQ, J (B310 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje CNHQfG GdTjN CHh GdaVd CMeO eJi fUQ Gddg EdG Ef fUQ Gddg bQjH hbGd jG CjgG GdPjf BefhG CPcQhG fYeg Gddg Ydjce s
(3BNQgG (B:s
(3bGd dfG QShd Gddg Udi Gddg Ydjg hSde(B: (3jG eYTQ ef Bef HdSGfg ade jONd GdEjeGf bdHg dGJZJGHhG GdeSdejf hdG JJHYhG YhQGJge aEfg ef GJHY YhQGJge JJHY Gddg YhQJg hef JJHY Gddg YhQJg jaVMg ai HjJg Je GdLRA HMeO Gddg hYhfg hUdi Gddg Ydi fHjfG eMeO hYds
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B4s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B147s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds